Intercultural Communication: Confronting conceptions and problems - Protzel, Javier (2015)
Interculturality, as an idea and as a fact, so present since the last decades of the last century, because of the increasing domestic and international migrations worldwide, entails conceptions which come to be too diverse as the prevailing cultures at the regions of exchange. These differences favor some viewpoints and political interests, disregarding others. This obstructs the generation of shared mainstream. And Latin America holds a singular position therein.